Do Strategic Reasoning and Brainstorming Help Auditors Change Their Standard Audit Procedures in Response to Fraud Risk? - Hoffman, Vicky B.; Zimbelman, Mark F. (The Accounting Review, 2009)
ABSTRACT: The Public Company Accounting Oversight Board recently reported that its inspections show that auditors fail to effectively modify their standard audit procedures in response to fraud risk. Prior academic research is consistent with this finding. Our study examines the effects of two interventions on auditors' planning decisions in a high-fraud-risk setting: strategic reasoning and brainstorming in groups. Both interventions are predicted to lead auditors to more effectively modify their planned audit procedures. We use a panel of fraud experts to identify effective modifications to the audit plan of a specific fraud case. The experts' recommendations are then used to evaluate the effectiveness of practicing auditors' audit plans with and without the two interventions. We predict and find that each intervention leads to more effective modifications to the standard audit procedures and that the combination of the interventions is not significantly more effective than either intervention used alone.